PHYSICO-MECHANICAL AND ANTIBACTERIAL PROPERTIES OF CHITOSAN AND POLYETHYLENE GLYCOL-BASED HYDROGEL FILMS - BILETSKA, HALYNA; YEFREMOVA, OLHA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article highlights the advantages of hydrogel wound-dressing materials compared to traditional textile ones. It is substantiated that, for the production of wound dressings, hydrogels must possess a high waters content, sufficient mechanical strength, and antibacterial properties. The results of the study of the physico-mechanical (swelling degree, tensile strength) and antibacterial properties of hydrogel films based on chitosan and polyethylene glycol are presented. It was found that films with a chitosan/polyethylene glycol ratio of 60/40 exhibit better absorption capacity for water and Ringer’s solution. The mineral filler – bentonite clay modified with silver ions, increases the swelling degree of the hydrogels. It was determined that the tensile strength of hydrogel films increases with a higher content of polyethylene glycol. The strongest tensile properties were observed in films with a chitosan / polyethylene glycol ratio of 40 / 60. Films containing bentonite clay modified with silver ions were nearly twice as strong as similar films without the mineral component. It was established that chitosan and polyethylene glycol-based hydrogel films possess antibacterial properties against both Gram-positive and Gram-negative bacteria. Films containing bentonite clay modified with silver ions demonstrated superior antibacterial activity compared to chitosan / polyethylene glycol films and more effectively inhibited bacterial growth. It is substantiated that hydrogel films with a chitosan / polyethylene glycol ratio of 50 / 50 have the optimal combination of swelling degree and mechanical strength. Incorporating bentonite clay modified with silver ions into the composition of hydrogel films increases their swelling degree, improves mechanical strength, and enhances antibacterial properties. Additionally, films containing bentonite clay absorb solutions with a chemical composition similar to biological fluids more effectively.